Long-term clinical outcomes of patients receiving proton beam therapy for caudate lobe hepatocellular carcinoma. (25th May 2021) - Iizumi, Takashi; Okumura, Toshiyuki; Sekino, Yuta; Takahashi, Hiroaki; Tsai, Yu-Lun; Takizawa, Daichi; Ishida, Toshiki; Hiroshima, Yuichi; Nakamura, Masatoshi; Shimizu, Shosei; Saito, Takashi; Numajiri, Haruko; et al.
Abstract: Hepatocellular carcinoma (HCC) located in the caudate lobe (caudate HCC) is rare; however, patients with this type of tumour have poorer prognoses than those with HCC in other segments. Despite many published reports on the clinical usefulness of proton beam therapy (PBT) for HCC, data on the clinical outcomes of patients undergoing PBT for caudate HCC remain scarce. Therefore, the present study aimed to investigate the outcomes of this group of patients. Thirty patients with caudate HCC who underwent definitive PBT between February 2002 and February 2014 were retrospectively analysed. The total irradiation doses ranged from 55 to 77 (median 72.6) Gy relative biological dose. The median follow-up period was 37.5 (range, 3.0–152.0) months. The overall survival (OS) rates at one, three and five years were 86.6%, 62.8% and 46.1%, respectively. According to univariate and multivariate analyses, Child-Pugh A ( P  < 0.01), having a single tumour ( P  = 0.02) and a low serum alpha-fetoprotein level (AFP; P  < 0.01) were significant factors predicting longer survival. The local control (LC) rates at one, three and five years were 100%, 85.9% and 85.9%, respectively, while the corresponding progression-free survival (PFS) rates were 65%, 27.5% and 22%, respectively. No grade 3 or worse adverse events were observed. PBT is effective and safe for the treatment of caudate HCC, and should therefore be considered a feasible option for intervention in patients with this disease.